2003
DOI: 10.1007/s00198-003-1433-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of bone mineral density in adults and children with Marfan syndrome

Abstract: Recent studies indicate that decreased bone mineral density (BMD) occurs in the spine, femoral necks and greater trochanters of some adults and children with Marfan syndrome. Because there is uncertainty regarding the BMD status of patients with Marfan syndrome, we undertook an analysis of BMD in both adults and children with Marfan syndrome. Dual energy X-ray absorptiometry analysis was performed on a convenience sample of 51 patients (30 adults and 21 children) with diagnosed Marfan syndrome from 1993 to 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 16 publications
0
22
0
1
Order By: Relevance
“…In a previously published study where BMD was assessed with a Lunar DPXL instrument [11], BMD measurements corresponding to osteopenia in the femoral neck of adult men with Marfan syndrome ( P < 0.001) were reported. Carter et al [10], using Hologic QDR1000 to assess BMD, also reported lower values for femoral neck BMD ( P < 0.05) in men whose average age was much younger compared to men in the study of Giampietro et al [11], although differences observed by this group were more pronounced. Conflicting results were obtained regarding BMD status in adult women with Marfan syndrome [6, 7, 911].…”
Section: Introductionmentioning
confidence: 99%
“…In a previously published study where BMD was assessed with a Lunar DPXL instrument [11], BMD measurements corresponding to osteopenia in the femoral neck of adult men with Marfan syndrome ( P < 0.001) were reported. Carter et al [10], using Hologic QDR1000 to assess BMD, also reported lower values for femoral neck BMD ( P < 0.05) in men whose average age was much younger compared to men in the study of Giampietro et al [11], although differences observed by this group were more pronounced. Conflicting results were obtained regarding BMD status in adult women with Marfan syndrome [6, 7, 911].…”
Section: Introductionmentioning
confidence: 99%
“…Other data indicated that MFS children have significantly lower BMC as well as whole-body and lumbar-spine BMD compared with controls that were matched for age, sex, height, and ethnicity [189]. In contrast, another study reported normal BMD at the lumbar spine and femoral neck in 21 MFS children [186]. …”
Section: Introductionmentioning
confidence: 99%
“…Several authors have observed reduced axial and peripheral bone mineral density (BMD) in adults (males and/or females) with MFS suggesting that these patients are at increased risk of fractures [Kohlmeier et al, 1993, 1995; Tobias et al, 1995; Le Parc et al, 1999; Carter et al, 2000; Giampietro et al, 2003, 2007; Moura et al, 2006]. Conversely, some authors did not find evidence of osteopenia [Gray et al, 1993].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, there is one study including children with MFS (n = 16), which showed low BMD at femoral neck and a trend towards reduced lumbar spine BMD [Kohlmeier et al, 1995]. Another study reported normal BMD in MFS children (n = 21) at lumbar spine and femoral neck [Giampietro et al, 2003]. Hence, it is unclear whether bone mineral density is low in children with MFS.…”
Section: Introductionmentioning
confidence: 99%